2021
DOI: 10.1158/1078-0432.ccr-21-2103
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-smooth Muscle Actin Expression in the Stroma Predicts Resistance to Trastuzumab in Patients with Early-stage HER2-positive Breast Cancer

Abstract: ◥Purpose: The companion diagnostic test for trastuzumab has not changed much in the last 25 years. We used high-plex digital spatial profiling to identify biomarkers besides HER2 that can help predict response to trastuzumab in HER2-positive breast cancer.Experimental Design: Fifty-eight protein targets were measured in three different molecularly defined compartments by the NanoString GeoMx Digital Spatial Profiler (DSP) in a tissue microarray containing 151 patients with breast cancer that received adjuvant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The high expression of α-smooth muscle actin (α-SMA) is another prominent characteristic of CAFs, and its expression level has been identified as a novel biomarker of resistance to trastuzumab early-stage of HER2-positive breast cancer [ 437 ]. Specific targeting α-SMA with docetaxel-conjugate nanoparticles increased drug delivery efficiency by enhancing vascular perfusion and reduced cancer metastases [ 438 ].…”
Section: Targeted Therapy Based On Tumor Stromamentioning
confidence: 99%
“…The high expression of α-smooth muscle actin (α-SMA) is another prominent characteristic of CAFs, and its expression level has been identified as a novel biomarker of resistance to trastuzumab early-stage of HER2-positive breast cancer [ 437 ]. Specific targeting α-SMA with docetaxel-conjugate nanoparticles increased drug delivery efficiency by enhancing vascular perfusion and reduced cancer metastases [ 438 ].…”
Section: Targeted Therapy Based On Tumor Stromamentioning
confidence: 99%
“…Specifically, the tissue sections of obese patients displayed a significantly higher αSMA level in stroma compared to the sections from lean patients. This is of specific importance, as it has been recently reported that the stromal expression of αSMA is highly associated with the resistance to trastuzumab in patients with early-stage Her2 positive breast cancer [ 95 ]. Additionally, the expression of αSMA was found to be correlated with poor prognosis in patients with ER positive breast cancer [ 96 ] and in patients with luminal breast cancer [ 97 ], likely mediated by a TMX resistance and an increased proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of heterogeneous variances, the Welch ANOVA and Games-Howell post hoc test were used for data analysis. Considering we performed multiple ANOVA, P values were corrected using the Benjamini–Hochberg method to control the false discovery rate (FDR) at 0.10, and the adjusted P value ( P .adjust) < 0.10 was considered statistically significant [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…Statistical significance was set at P < 0.05; statistical trends were set at P < 0.10. Since we performed a large number of regressions between cognitive function and topographical spindle characteristics, the Benjamini and Hochberg method was used to correct the P values, and P .adjust < 0.10 was considered still statistically significant after correction [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%